Telomeres and sirtuins: at the end we meet again - Hisayuki Amano; Ergun Sahin (Molecular & Cellular Oncology, 2019)
Telomeres and sirtuins are independently implicated in causing disease and aging, but how they cooperate is not well understood. A recent study demonstrates that telomere shortening represses sirtuins and increasing sirtuin activity stabilizes telomeres and improves telomere-dependent disease, suggesting that these two pathways are tightly intertwined.